Current Concepts in Dental Implantology From Science to Clinical Research - Gabrić, Dragana; Vuletić, Marko (Dentistry, 2022)
Current Concepts in Dental Implantology - From Science to Clinical Research presents comprehensive information on all modern scientific and clinical methods used in today's dental implantology. Chapters address such topics as osseointegration and basic science in dental implantology, current trends and biomaterials of clinical relevance, advanced clinical techniques, peri-implantitis, and prosthodontic trends in dental implantology. This book provides a better understanding of the scientific approach to basic concepts in dental implantology and presents the results of many clinical studies.